Untargeted GC-MS and FT-NIR study of the effect of 14 processing methods on the volatile components of Polygonatum kingianum - Xu, Yulin; Yang, Meiquan; Yang, Tianmei; Yang, Weize; Wang, Yuanzhong; Zhang, Jinyu (Frontiers in Plant Science, 2023)
Polygonatum kingianum is a traditional medicinal plants, and processing has a significant impact on its quality. Therefore, untargeted gas chromatography-mass spectrometry (GC-MS) and Fourier transform-near-infrared spectroscopy (FT-NIR) were used to analyze the 14 processing methods of commonly used in the Chinese market. It is dedicated to analysing the causes of major volatile metabolite changes and identifying signature volatile components for each processing method. A total of 333 metabolites were identified by the untargeted GC-MS technique. The relative content accounted for sugars (43%), acids (20%), amino acids (18%), nucleotides (6%), and esters (3%). The multiple steaming and roasting samples contained more sugars, nucleotides, esters, flavonoids, but less amino acids. The sugars are predominantly monosaccharides or small molecular sugars, mainly due to polysaccharides depolymerisation. The heat treatment reduces the amino acid content significantly and the multiple steaming and roasting methods are not conducive to the accumulation of amino acids. The multiple steaming and roasting samples showed significant differences, as seen from principal component analysis (PCA) and hierarchical cluster analysis (HCA) based on GC-MS and FT-NIR. The partial least squares discriminant analysis (PLS-DA) based on FT-NIR can achieve 96.43% identification rate for the processed samples. This study can provide some references and options for consumers, producers, and researchers.